2014
DOI: 10.48550/arxiv.1407.1170
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incentive and stability in the Rock-Paper-Scissors game: an experimental investigation

Abstract: In a two-person Rock-Paper-Scissors (RPS) game, if we set a loss worth nothing and a tie worth 1, and the payoff of winning (the incentive a) as a variable, this game is called as generalized RPS game. The generalized RPS game is a representative mathematical model to illustrate the game dynamics, appearing widely in textbook. However, how actual motions in these games depend on the incentive has never been report quantitatively. Using the data from 7 games with different incentives, including 84 groups of 6 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…That is, the deterministic motions are faster in the social state close to the simplex edge than those close to the rest point. This result was previously unknown; moreover, such clear and high-precision empirical patterns have not been seen [23,26,24,17]. We use the observed values in each patch to evaluate the theoretical models.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…That is, the deterministic motions are faster in the social state close to the simplex edge than those close to the rest point. This result was previously unknown; moreover, such clear and high-precision empirical patterns have not been seen [23,26,24,17]. We use the observed values in each patch to evaluate the theoretical models.…”
Section: Resultsmentioning
confidence: 95%
“…Naturally, the reality of evolutionary dynamics models have been widely considered [27,28,29,30]. In recent decades, social scientists have continued to investigate and improve upon the commonalities between models and experiments [18,19,11,20,21,22,17,23,24,25,26]. However, there is still a significant gap between evolutionary outcomes from models and empirical results.…”
Section: Research Questionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the experiment each population plays with a fixed reward parameter a whose value ranging from a = 1.1 to a = 100. The empirical results demonstrated that the precise value of a does not affect the qualitative dynamical behaviour of this finite-population system [20,30].…”
Section: Conditional Response Patterns In Human Subjectsmentioning
confidence: 95%